Mogroside V Alleviates Oocyte Meiotic Defects and Quality Deterioration in Benzo(a)pyrene-Exposed Mice - Sui, Lumin; Yan, Ke; Zhang, Huiting; Nie, Junyu; Yang, Xiaogan; Xu, Chang-Long; Liang, Xingwei (Frontiers in Pharmacology, 2021)
Accumulating evidence has demonstrated that benzo(a)pyrene (BaP) exposure adversely affects female reproduction, especially oocyte meiotic maturation and subsequent embryo development. Although we previously found that mogroside V (MV), a major bioactive component of S. grosvenorii, can protect oocytes from quality deterioration caused by certain stresses, whether MV can alleviate BaP exposure-mediated oocyte meiotic defects remains unknown. In this study, female mice were exposed to BaP and treated concomitantly with MV by gavage. We found that BaP exposure reduced the oocyte maturation rate and blastocyst formation rate, which was associated with increased abnormalities in spindle formation and chromosome alignment, reduced acetylated tubulin levels, damaged actin polymerization and reduced Juno levels, indicating that BaP exposure results in oocyte nucleic and cytoplasmic damage. Interestingly, MV treatment significantly alleviated all the BaP exposure-mediated defects mentioned above, indicating that MV can protect oocytes from BaP exposure-mediated nucleic and cytoplasmic damage. Additionally, BaP exposure increased intracellular ROS levels, meanwhile induced DNA damage and early apoptosis in oocytes, but MV treatment ameliorated these defective parameters, therefore it is possible that MV restored BaP-mediated oocyte defects by reducing oxidative stress. In summary, our findings demonstrate that MV might alleviate oocyte meiotic defects and quality deterioration in BaP-exposed mice.